2001
DOI: 10.1146/annurev.biophys.30.1.271
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting the Effects of Small Uncharged Solutes on Protein-Folding Equilibria

Abstract: Proteins are designed to function in environments crowded by cosolutes, but most studies of protein equilibria are conducted in dilute solution. While there is no doubt that crowding changes protein equilibria, interpretations of the changes remain controversial. This review combines experimental observations on the effect of small uncharged cosolutes (mostly sugars) on protein stability with a discussion of the thermodynamics of cosolute-induced nonideality and critical assessments of the most commonly applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
262
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 269 publications
(274 citation statements)
references
References 92 publications
(135 reference statements)
11
262
0
1
Order By: Relevance
“…Both studies showed that B 23 decreases in systems where the small molecules interact favorably with the test protein and increases in systems when there is enhanced repulsion. A more detailed assessment of second virial coefficients for small osmolytes is given by Davis-Searles et al (2001).…”
Section: Measuring Excluded Volumementioning
confidence: 99%
“…Both studies showed that B 23 decreases in systems where the small molecules interact favorably with the test protein and increases in systems when there is enhanced repulsion. A more detailed assessment of second virial coefficients for small osmolytes is given by Davis-Searles et al (2001).…”
Section: Measuring Excluded Volumementioning
confidence: 99%
“…However, retention of the biological activity of a protein or other biomolecule in the course of this (or any mass spectrometry experiment) is a much more challenging problem. This is the subject addressed in the present paper through the combined choice of gentle ionization methods and an appropriate liquid surface for soft-landing.It is well known that polyols and sugars can efficiently stabilize a protein in an otherwise denaturating environment [15,16], although the underlying mechanism of this process has not been elucidated. Lakshmi and Nandi [17] in 1976 showed that sucrose and glucose decrease the solubility of phenylalanine, tyrosine, and tryptophan in aqueous solution and suggested that this was due to increased hydrophobic interactions.…”
mentioning
confidence: 99%
“…Along similar lines, considering protein molecules, a solution of 40 % PEG (mol wt 400 g/mol) leads to a 9 % reduction in the volume of superoxide dismutase (Rajapaksha et al 2015). Enhanced self-association, susceptibility to compact folding states and stabilization against thermal denaturation of certain proteins, are also noted in relation to co-solute polyol size and concentration (Ogston and Winzor 1975;Shearwin and Winzor 1988;Wills et al 1993;Davis-Searles et al 2001). To the best of our knowledge, direct consequences of crowding-induced osmotic forces on biomineral nucleation and growth have not been investigated; however, certain insights can be drawn from the existing literature.…”
Section: Osmotic Conditions In Niche Spacesmentioning
confidence: 85%
“…Under such conditions, the equilibrium constants for protein self-association can change by tens of orders of magnitude depending on the activity coefficient of associating species, which in turn depends on the concentration, shape and molar mass distribution of macromolecules (Zimmerman and Trach 1991). Deviations in protein equilibria and stability are also identified for high concentrations of small co-solutes such as polyols (Davis-Searles et al 2001;Patel et al 2002). From this perspective, it is important to study metabolic and regulatory pathways in living systems in the context to the actual physio-chemical environments.…”
Section: Facets Of Biophysical Non-idealitymentioning
confidence: 99%
See 1 more Smart Citation